Simulation training methods in mastering the skills of emergency medical carev (Herald of the National Children's Medical Center, 2024)
Abstract: There are results were analyzed: students' perception and digestibility of educational material on emergency pediatrics using simulation equipment.Materials and methods of research: Simulation training is a relatively new and very rapidly developing area of medical education.Results of the study: This teaching method is especially important for mastering the skills of emergency and emergency care for children.Conclusion: High demands on the quality of training of doctors, limited opportunities to work out new practical skills on patients (especially children), increased attention to the safety of medical care for patients and medical personnel, and adherence to ethical standards led to a new paradigm of medical education - the use of simulation methods of training.
Keywords: higher medical education; pedagogical technologies; competence approach; simulation training